An annotated checklist of oribatid mites (Acari: Oribatida) of Iran - Akrami, Mohammad Ali (Zootaxa, 2015)
Oribatid mites (Acari: Oribatida) are one of the largest and dominating groups of soil inhabitants that play an important role in the formation and fertilization processes of the soils. In the present paper, a list of oribatid mites of Iran (excluding Astigmata) is present based mainly on the collected and identified species and on literature records since 1961. In total, 380 species belonging to 191 genera and 86 families have been recorded and these are listed along with their known geographical distributions and localities in Iran. The following seven species Sellnickochthonius cricoides (Weis-Fogh, 1948), Hypochthoniella minutissima (Berlese, 1904), Nothrus silvestris Nicolet, 1855, Hemileius (Hemileius) initialis (Berlese, 1908), Punctoribates (Punctoribates) punctum (C. L. Koch, 1839), Ceratozetes conjunctus Mihelčič, 1956, Eupelops tardus (C. L. Koch, 1835) and Pelopsis Hall, 1911 are recorded for the first time from Iran. The closing date for publications included in this list was 15 January 2015.